ECONOMIC FEASIBILITY OF LETTUCE INTERCROPPED WITH ROCKET IN FUNCTION OF SPACING AND GROWING SEASON - Nascimento, Carolina Seno [UNESP]; Nascimento, Camila Seno [UNESP]; Cecilio Filho, Arthur Bernardes [UNESP] (Univ Fed Rural Semi-arido-ufersa, 2018)
Intercropping is a production system that can reduce the production cost and increase the profitability of vegetable producers, since it permits more efficient land and agricultural inputs use. In order to evaluate the effect of lettuce plant density on the economic feasibility of lettuce-rocket intercropping system over two growing seasons (winter and summer), two experiments were conducted in the field at Sao Paulo State University Julio de Mesquita Filho (UNESP), Jaboticabal, Sao Paulo, Brazil. The treatments consisted of five lettuce-rocket intercrops with spacing between lettuce rows of: 0.20; 0.25; 0.30; 0.35 and 0.40 m, five sole crop of lettuce in the same spacing between rows adopted in the intercropping system, and a sole cropping of rocket with spacing between rows of 0.20 m. The statistical design adopted was the complete randomized block with four replicates. During winter, higher profitability was achieved with the highest population density. Highest profitability of the crops in both seasons was obtained in summer.
Keywords: Eruca sativa; Lactuta sativa; Profitability; Growth system